2012
DOI: 10.1111/j.1757-5672.2011.00125.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Renin‐Angiotensin System on the Obstructed Bladder

Abstract: Bladder hypertrophy and dysfunction are well-known bladder responses to outlet obstruction (i.e. urodynamic overload). Cardiac hypertrophy and heart failure are also caused by hemodynamic overload, and many basic and clinical studies suggest that the local renin-angiotensin system (RAS) has a crucial role in load-induced cardiac pathogenesis. The similarity of the response of the heart and the bladder to overload suggests that angiotensin II (AngII) may have a similar regulatory role in pathological remodeling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…In previous reports, Wiseman et al reported that flavonoid-rich blueberries could inhibit angiotensin-converting enzyme activity [29]. Also, Aikawa et al reported that angiotensin receptor blockers prevented the development of DO in BOO rats [30]. These results indicate that the administration of angiotensin receptor blockers significantly suppressed bladder weight increase and bladder smooth muscle layer fibrosis in BOO rats.…”
Section: Discussionmentioning
confidence: 82%
“…In previous reports, Wiseman et al reported that flavonoid-rich blueberries could inhibit angiotensin-converting enzyme activity [29]. Also, Aikawa et al reported that angiotensin receptor blockers prevented the development of DO in BOO rats [30]. These results indicate that the administration of angiotensin receptor blockers significantly suppressed bladder weight increase and bladder smooth muscle layer fibrosis in BOO rats.…”
Section: Discussionmentioning
confidence: 82%
“…Consequently, this opens perspectives to use inhibitors of the angiotensin II activity in the clinical management of some urologic disorders . Angiotensin II is also a local trophic factor that is involved in the development of load‐induced bladder hypertrophy, for example, in patients with bladder outlet obstruction . Furthermore, sex hormones also seem to influence the local RAS in the bladder, as recently published by Nakazawa et al In their experiments on rats, they observed a correlation between androgen status and expression of AT2 receptors (angiotensin II receptor type 2) and apoptosis‐related proteins in the bladder.…”
mentioning
confidence: 71%
“…Local RAS in the bladder enhances detrusor contractions through the action of angiotensin II . Consequently, this opens perspectives to use inhibitors of the angiotensin II activity in the clinical management of some urologic disorders .…”
mentioning
confidence: 99%
“…The obtained results indicate a small number of studies on this topic [4,13]. Basically, in the majority of scientific works, stem cells were used for the purpose of tissue engineering [2,14], the effect of increased contractility of UB and endogenous NFs, growth factors on the morphology and function of the urinary tract [12,[15][16][17][18], the effect of high hydrostatic pressure on different cell cultures [19], the role of NFs in neurodegenerative diseases [5,20]. The increased interest in this topic was caused by the results we obtained in previous works.…”
Section: Discussionmentioning
confidence: 98%